Safety and efficacy of endoscopic spray cryotherapy for Barrett's esophagus with high-grade dysplasia - Shaheen, Nicholas J.; Greenwald, Bruce D.; Peery, Anne F.; Dumot, John A.; Nishioka, Norman S.; Wolfsen, Herbert C.; Burdick, J. Steven; Abrams, Julian A.; Wang, Kenneth K.; Mallat, Damien; Johnston, Mark H.; Zfass, Alvin M.; et al. (Gastrointestinal endoscopy, 2010)
Endoscopic ablation to treat Barrett's esophagus (BE) with high-grade dysplasia (HGD) is associated with a decreased incidence of esophageal adenocarcinoma. Endoscopic spray cryotherapy (CRYO) demonstrates promising preliminary data. To assess the safety and efficacy of CRYO in BE with HGD. Multicenter, retrospective cohort study. Nine academic and community centers; treatment period, 2007 to 2009. Subjects with HGD confirmed by 2 pathologists. Previous EMR was allowed if residual HGD remained. CRYO with follow-up biopsies. Complete eradication of HGD with persistent low-grade dysplasia, complete eradication of all dysplasia with persistent nondysplastic intestinal metaplasia, and complete eradication of all intestinal metaplasia. Ninety-eight subjects (mean age 65.4 years, 83% male) with BE and HGD (mean length 5.3 cm) underwent 333 treatments (mean 3.4 treatments per subject). There were no esophageal perforations. Strictures developed in 3 subjects. Two subjects reported severe chest pain managed with oral narcotics. One subject was hospitalized for bright red blood per rectum. Sixty subjects had completed all planned CRYO treatments and were included in the efficacy analysis. Fifty-eight subjects (97%) had complete eradication of HGD, 52 (87%) had complete eradication of all dysplasia with persistent nondysplastic intestinal metaplasia, and 34 (57%) had complete eradication of all intestinal metaplasia. Subsquamous BE was found in 2 subjects (3%). Nonrandomized, retrospective study with no control group, short follow-up (10.5 months), lack of centralized pathology, and use of surrogate outcome for decreased cancer risk. CRYO is a safe and well-tolerated therapy for BE and HGD. Short-term results suggest that CRYO is highly effective in eradicating HGD.